2021
DOI: 10.7554/elife.65534
|View full text |Cite
|
Sign up to set email alerts
|

High infectiousness immediately before COVID-19 symptom onset highlights the importance of continued contact tracing

Abstract: Background:Understanding changes in infectiousness during SARS-COV-2 infections is critical to assess the effectiveness of public health measures such as contact tracing.Methods:Here, we develop a novel mechanistic approach to infer the infectiousness profile of SARS-COV-2-infected individuals using data from known infector–infectee pairs. We compare estimates of key epidemiological quantities generated using our mechanistic method with analogous estimates generated using previous approaches.Results:The mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(87 citation statements)
references
References 49 publications
(141 reference statements)
5
82
0
Order By: Relevance
“…Compared to the ODE model, SIMCoV produced a less pronounced peak with higher viral loads early in infection that persisted for several days. The SIMCoV curves are consistent with the observation that individuals infected with SARS-CoV-2 are most infectious early in infection before symptom onset [39,40]. The SIMCoV runs also predict that elevated viral titers persist for more days, which agrees with patient viral load data.…”
Section: Plos Computational Biologysupporting
confidence: 81%
“…Compared to the ODE model, SIMCoV produced a less pronounced peak with higher viral loads early in infection that persisted for several days. The SIMCoV curves are consistent with the observation that individuals infected with SARS-CoV-2 are most infectious early in infection before symptom onset [39,40]. The SIMCoV runs also predict that elevated viral titers persist for more days, which agrees with patient viral load data.…”
Section: Plos Computational Biologysupporting
confidence: 81%
“…It is clear that more research is needed on this topic to correlate viral load with symptoms and clinical outcomes (Mahallawi et al, 2021). Hart et al (2021) showed that about 65% of virus transmission occurs before symptoms develop. Thus, individuals circulate in the general community before their infections are detected (Hart et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“… Hart et al (2021) showed that about 65% of virus transmission occurs before symptoms develop. Thus, individuals circulate in the general community before their infections are detected ( Hart et al, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Isolation of nonsymptomatic hosts was more effective at reducing the local outbreak probability than isolation of symptomatic hosts ( Figs 6 A,B), although of course this is more challenging to achieve ( Lovell-Read et al, 2021 ). However, if fast isolation of nonsymptomatic hosts could be achieved through efficient large-scale testing (potentially in combination with contact tracing ( Hart et al, 2021 ), the probability of local outbreaks could be reduced substantially through this measure alone.…”
Section: Resultsmentioning
confidence: 99%